2019
DOI: 10.1186/s40168-019-0766-7
|View full text |Cite
|
Sign up to set email alerts
|

Discordant transmission of bacteria and viruses from mothers to babies at birth

Abstract: BackgroundThe earliest microbial colonizers of the human gut can have life-long consequences for their hosts. Precisely how the neonatal gut bacterial microbiome and virome are initially populated is not well understood. To better understand how the maternal gut microbiome influences acquisition of the infant gut microbiome, we studied the early life bacterial microbiomes and viromes of 28 infant twin pairs and their mothers.ResultsInfant bacterial and viral communities more closely resemble those of their rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
95
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(109 citation statements)
references
References 48 publications
6
95
0
Order By: Relevance
“…Recently, the metagenomic sequencing analysis of stool samples of several cohorts of healthy neonates revealed a stepwise viral colonization model wherein prophages may be the viral pioneers in the gut at one month after birth while, by four months, eukaryotic viruses became prominent [22][23][24]. The first several years of life are then a particularly dramatic period of co-infection, and the simultaneous detection of multiple enteropathogens is common, both associated with AGE and even in the absence of symptoms.…”
Section: Virus-virus Co-infection Prevalencementioning
confidence: 99%
“…Recently, the metagenomic sequencing analysis of stool samples of several cohorts of healthy neonates revealed a stepwise viral colonization model wherein prophages may be the viral pioneers in the gut at one month after birth while, by four months, eukaryotic viruses became prominent [22][23][24]. The first several years of life are then a particularly dramatic period of co-infection, and the simultaneous detection of multiple enteropathogens is common, both associated with AGE and even in the absence of symptoms.…”
Section: Virus-virus Co-infection Prevalencementioning
confidence: 99%
“…Recently, viruslike particle (VLP) enrichment and subsequently metagenomic sequencing provided a prospective application for fully delineating the gut virome [22,23]. Based on the VLP technique, studies had showed that the normal gut virome was partly inherited from mother [24,25], potentially transferred between twins [4], and continuously expanded during the rst years of life [21]. In addition, longitudinal analysis revealed that the gut virome of healthy adults was highly diverse, temporally stable, and individually speci c [14].…”
Section: Introductionmentioning
confidence: 99%
“…Intestinal virome is large and diverse, but nonetheless stable and highly personalized [1,73], established in the earliest period of human life simultaneously with the colonization of bacteria and other constituents of the gut microbiota [74]. The gut virome in the neonatal period predominantly consists of bacteriophages, with only a small fraction of eukaryotic viruses, and akin to the bacterial microbiome, it significantly varies across individuals [75]. In contrast to research on bacteria and fungi, no universal marker gene can be utilized to study viruses and the majority of obtained sequences do not exist in publicly available databases ("viral dark matter" [76,77]), so the usual methodological approach of virome research is metagenomics.…”
Section: Human Viromementioning
confidence: 99%